Species Diversity and Nutritional Potential of Grasshoppers (Orthoptera: Caelifera) Associated with Agroecosystems in Thailand - Korkoonklang, Jeerasak; Nuchchanart, Wirawan; Taekul, Charuwat; Yoiphakwaend, Kittayawan; Sanguansub, Sunisa (AGRIVITA Journal of Agricultural Science, 2026)
Grasshoppers (Orthoptera: Caelifera) have increased interest as sustainable protein sources due to their high nutritional composition and their ecological roles. This study employed sweep-net sampling (100 sweeps along a 100-meter transect per site per event) to examine grasshopper diversity, abundance, and nutrition across six Thai agroecosystems. Diversity indices were investigated, and nutritional values were identified using AOAC methods. A total of 3,400 individuals from 23 species were collected. Paddy fields and grass floors were the most diverse species and abundant, especially in the Northeast and Central areas. Three diversity indices, Shannon–Wiener (1.9–2.7), Simpson (0.86–0.93), Pielou’s evenness (0.80–0.94), and species richness (8–16), showed moderate diversity with some habitat dominance. GLM suggested that both habitats and regions significantly influenced their abundance, and rarefaction studies validated sample adequacy. Nutritional analysis of five abundant species showed high levels of crude protein (70–79% dry matter). Pseudoxya diminuta, Spathosternum prasiniferum, and Ceracris fasciata showing superior nutritional profiles. Spathosternum prasiniferum was particularly high in calcium and phosphorus. These results show which species and habitats are sustainable for future protein production by combining ecological and nutritional perspectives. Such insights can support integrated grasshopper farming, farmer income diversification, and sustainable protein development in Thailand.